Influence of Material Composition on Flame Spread Behaviour over Combustible Solid of Paper/Bagasse - Ramli, Afifah; Razali, Mohd Azahari; Madon, Rais Hanizam; Hushim, Mohd Faisal; Khalid, Amir; Mohmad Ja'at, Md Norrizam; Salleh, Hamidon (International Journal of Integrated Engineering, 2018)
Fire Safety Engineering is an application of science to improve the safety from the destructive effect of the fire. Paper is one of sources creating fire, however, research on flame spread towards paper is still not enough to describe about the phenomenon. Inspiration from this, the behavior of downward flame spread over paper/bagasse is experimentally investigated. Composition of 0%, 30%, 50%, 70% and 100% bagasse is determined for this research. Flame spread behavior for each composition is analyzed from the observation. Results show for each composition, the flame spreads with â€œUâ€ shape at the beginning of combustion until the whole specimen. The result also shows that the flame spread rate decreases as bagasse composition increases. The highest flame spread is 0.8133 mm/s for pure paper and the lowest one is 0.4814 mm/s for pure bagasse. It infers that the flame spread shape and rate is influenced by the bagasse composition and density, respectively. Â